2020
DOI: 10.1080/09669582.2020.1849230
|View full text |Cite
|
Sign up to set email alerts
|

Whose right to the city? An analysis of the mediatized politics of place surrounding alojamento local issues in Lisbon and Porto

Abstract: In view of the proliferation of alojamento local (short-term vacation rentals) in the major Portuguese cities of Lisbon and Porto, along with the recent transformation of the historic city centre neighbourhoods, this study explores the mediatized politics of place by analysing data sets resulting from different, but interconnected, discursive practices. At the level of governance, we examine how legislation has enabled and facilitated this transformation. We then explore the media coverage of the issues surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Ryan and Ma (2020) contribution presents the example of Raglan in New Zealand, a small coastal town, in which STRs have affected several dimensions of place attachment and identity. Torkington and Ribeiro (2020) on Lisbon and Porto, as well as Muschter et al (2020) on Byron Shire in New South Wales, Australia, expand the discussion on the transformation of public spaces as centres of leisure and entertainment. Many of the authors in this collection (Cheng et al, 2020;Muschter et al, 2020;Ryan & Ma, 2020;Salerno & Russo, 2020;Torkington & Ribeiro, 2020;Wilson et al, 2020) have observed an increased perception of risk, noise and discomfort from living in places where residents can no longer recognise their neighbours.…”
Section: Themes Addressed In This Special Issuementioning
confidence: 96%
See 3 more Smart Citations
“…Ryan and Ma (2020) contribution presents the example of Raglan in New Zealand, a small coastal town, in which STRs have affected several dimensions of place attachment and identity. Torkington and Ribeiro (2020) on Lisbon and Porto, as well as Muschter et al (2020) on Byron Shire in New South Wales, Australia, expand the discussion on the transformation of public spaces as centres of leisure and entertainment. Many of the authors in this collection (Cheng et al, 2020;Muschter et al, 2020;Ryan & Ma, 2020;Salerno & Russo, 2020;Torkington & Ribeiro, 2020;Wilson et al, 2020) have observed an increased perception of risk, noise and discomfort from living in places where residents can no longer recognise their neighbours.…”
Section: Themes Addressed In This Special Issuementioning
confidence: 96%
“…The entanglement of urban entrepreneurialism and digital platforms has manifested itself in what Filip Stabrowski (2017) calls "spaces of domestic entrepreneurialism" -that is, homes and neighbourhoods where people have adopted an entrepreneurial attitude. As Torkington and Ribeiro (2020) show in this issue, this is especially evident among young people who are renting apartments to tourists or temporary residents as part of their flexible lifestyles, which involve the accumulation of economic and social capital for the purpose of maintaining cosmopolitan cultural identities and making individualist decisions. This view of individualism and cosmopolitanism is aligned with an imaginary of a post-work and post-capitalist society, in which automation and robotics are freeing people from the oppressiveness of capitalist working conditions to enjoy leisure activities and self-actualisation (Snape et al, 2017).…”
Section: The Emergence Of Digital Platforms As Drivers Of Tourism Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only does overtourism cause damage to the historic part of a city and reduce the level of consumption of tourist experiences [20], but it also contributes to deteriorating the quality of life of the city inhabitants-for instance, by increasing the noise level, overcrowding and pollution, impeding access to certain public spaces and raising the cost of living [21]-and gives rise to tourism-phobia and tourism gentrification [20,22,23]. Increased tourist traffic and its negative impact on the oldest historic part of the city was noted by researchers in Polish cities such as Krakow [20] and Poznan [19], and in the world-in Berlin [17], Venice [22], Barcelona [24], Lisbon [25], and Porto [26]. Excessive tourist traffic can be prevented by sustainable urban tourism [12] the development of which is underlain by improving the functionality of the city transport infrastructure, beautifying public space and diversifying tourist traffic through expanding the cultural and gastronomic offer and creating all sorts of attractions in other parts of the city, redirecting tourist traffic to those parts, and creating new spaces attractive to tourists [27,28].…”
Section: Introductionmentioning
confidence: 99%